2020
DOI: 10.1021/acsptsci.0c00039
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Helix-8 and C-Terminal Tail in Regulating Proteinase Activated Receptor 2 Signaling

Abstract: The C-terminal tail of G-protein-coupled receptors (GPCR) contain important regulatory sites that enable interaction with intracellular signaling effectors. Here we examine the relative contribution of the C-tail serine/threonine phosphorylation sites (Ser383–385, Ser387–Thr392) and the helix-8 palmitoylation site (Cys361) in signaling regulation downstream of the proteolytically activated GPCR, PAR2. We examined Gαq/11-coupled calcium signaling, β-arrestin-1/-2 recruitment, and MAPK activation (p44/42 phospho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…As expected, neither trypsin nor SplB was able to induce ERK phosphorylation in cells lacking PAR2 ( Figure 2E). In recent work, we demonstrated that PAR2-mediated ERK phosphorylation in HEK293 cells occurs downstream of Gα q/11 signaling (56), and this is consistent with the observations that SplB stimulation of PAR2 does not induce Gα q/11 signaling.…”
Section: Mapksupporting
confidence: 90%
“…As expected, neither trypsin nor SplB was able to induce ERK phosphorylation in cells lacking PAR2 ( Figure 2E). In recent work, we demonstrated that PAR2-mediated ERK phosphorylation in HEK293 cells occurs downstream of Gα q/11 signaling (56), and this is consistent with the observations that SplB stimulation of PAR2 does not induce Gα q/11 signaling.…”
Section: Mapksupporting
confidence: 90%
“…In keeping with other Rhodopsin family GPCRs, a highly conserved amphipathic H8 [4,48] is seen within the PAR C-terminal domain (Figure 1), though this structure was not resolved in the PAR1 crystal structure. In PAR1 and PAR2, the H8 is critically stabilized through anchoring to the plasma membrane by palmitoylation of the C-terminal cysteine residues [49][50][51][52] as seen in a large number of other GPCRs [53,54]. PAR3 has an unusually short C-terminal tail (13 amino acids), while the PAR4…”
Section: Accepted Articlementioning
confidence: 99%
“…Similar interactions appear to be involved in PAR activation of -arrestins and G proteins. Destabilization of the H8 by mutation of cysteine and other amino acids in PAR1 [49], PAR2 [52] and PAR4 [55] to alanine negatively impact G q/11 coupling, and in the case of PAR2 and PAR4, -arrestin-1 and -2 recruitment. Additional intracellular interactions are also likely for PAR interaction with G proteins and -arrestins.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations